GIVING MEDICINE THROUGH INTRAVENOUS TOWARDS INCIDENT OF PHLEBITIS TO HOSPITALIZED PATIENT IN HOSPITAL - Iradiyanti, Winda Pratama; Kurnia, Erlin (Jurnal Penelitian STIKES Kediri, 2013)
Phlebitis incident is a reflection of the character of health care. The sign of phlebitis include an increase of skin temperature on the veins, pain, and some cases of redness in the site of insertion or along the vein line. The purpose of this research to study the phlebitis caused. The design used was cross sectional. Population of this research was all patients hospitalized at inpatient ward Kediri Baptist Hospital and all the nurses who provided medication through an intravenous tube at Kediri Baptist Hospital. The sample used was purposive sampling and the number of respondents was 23 people. The independent variable in this research was intravenous medicine application and aseptic techniques. The dependent variable was phlebitis. The data collection used in this research was observation sheet (checklist). The results 100% of nurses gave intravenous medicine with inappropriate speed, 74% of nurses do inappropriate in washing hands, 100% of respondents did not experience phlebitis. Conclusion of this research is medicine administering factor throughout intravenous tube had no effect on phlebitis, there is no dominant caused factor of phlebitis in this research.